2016
DOI: 10.1002/chem.201603974
|View full text |Cite
|
Sign up to set email alerts
|

Production of Pure Aqueous 13C‐Hyperpolarized Acetate by Heterogeneous Parahydrogen‐Induced Polarization

Abstract: Supported metal catalyst was designed, characterized and tested for aqueous phase heterogeneous hydrogenation of vinyl acetate with parahydrogen to produce 13C-hyperpolarized ethyl acetate for potential biomedical applications. The Rh/TiO2 catalyst with 23.2 wt% loading produced strong hyperpolarized 13C-enriched ethyl acetate-1-13C detected at 9.4 T. Approximately 14-fold 13C signal enhancement was detected using ~50% parahydrogen gas without taking into account relaxation losses before and after polarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 48 publications
2
56
0
2
Order By: Relevance
“…The use of a supported catalyst would allow to obtain complete removal of the toxic metal from the solution of the hyperpolarized product and to recover the expensive catalyst, and the development of these catalysts will be an important step towards the clinical translation perspective. [22] In this work, the phase transfer method has been applied. [23] According to this procedure, the lipophylic substrate is hydrogenated in an organic, hydrophobic solvent, (e.g.…”
Section: Hyperpolarized L-[1-c]lactatementioning
confidence: 99%
“…The use of a supported catalyst would allow to obtain complete removal of the toxic metal from the solution of the hyperpolarized product and to recover the expensive catalyst, and the development of these catalysts will be an important step towards the clinical translation perspective. [22] In this work, the phase transfer method has been applied. [23] According to this procedure, the lipophylic substrate is hydrogenated in an organic, hydrophobic solvent, (e.g.…”
Section: Hyperpolarized L-[1-c]lactatementioning
confidence: 99%
“…The equipment was tested on the parahydrogen addition product of 2-hydroxyethyl acrylate-1- 13 C- d 3 , whereupon conversion of the initial singlet state of nascent protons to net heteronuclear magnetization, 13 C polarization P was estimated to be 20 % ± 2.5 % corresponding to 13 C signal enhancement of approximately 25-million-fold at this reference low field of 9.1 mT or approximately 77,000-fold at 3 T with respect to thermally induced polarization at room temperature. The central control of the hyperpolarization could also be useful for non-hydrogenative PHIP experiments [43, 64, 7880] as well as in the context heterogeneous PHIP experiments [81, 82]. For biomedical applications, we anticipate that this design will be especially useful to laboratories already equipped with low field imaging consoles, and additionally, for basic science applications this polarizer design should facilitate translation of PASADENA to multidimensional NMR experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of lactate, it was demonstrated that, after the polarization procedure, lactate can enzymatically be converted into pyruvate . So far, the most successful approach of hyperpolarizing metabolites with para ‐hydrogen relies on a field cycling technique, for which 13 C polarization values of about 5 % have been experimentally demonstrated in highly concentrated solutions of acetate and pyruvate . The theoretical polarization limits of the field cycling technique have been investigated and simulations for an ideal case have shown that more than 30 % 13 C polarization can be achieved in the precursor molecule (before cleavage), whereas 50 % was suggested experimentally …”
Section: Figurementioning
confidence: 99%